Pengaruh Pengelolaan Kelas Dan Variasi Gaya Mengajar Guru Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X Di SMAN 5 Padang - Dessyta Gumanti; Caterina Lo; Verti Aprina Nehe (JURNAL ARMADA PENDIDIKAN, 2025)
The purpose of this study was to see the effect of classroom management and variations in teacher teaching styles on student learning outcomes in class X economics at SMAN 5 Padang. This type of research is a quantitative approach. The population in this study were all class X students at SMAN 5 Padang. Sampling using the Proportionate Random Sampling technique, so the sample obtained was 80 students. The results of this study indicate that there is an effect of classroom management (X_1) and variations in teacher teaching styles (X_2) on student learning outcomes (Y) in class X economics at SMAN 5 Padang. The significance value for the influence of (X_1) and (X_2) simultaneously on Y is 0.005 <0.05 and the F-count value is 4.894> Ftable 3.115. This shows that there is an effect of classroom management and variations in teacher teaching styles simultaneously on student learning outcomes (Y) in class X economics at SMAN 5 Padang